Important parameters affecting quality of vitrified donor oocytes - Teplá, Olga; Topurko, Zinovij; Mašata, Jaromír; Jirsová, Simona; Frolíková, Michaela; Komrsková, Kateřina; Minks, Adela; Turánek, Jaroslav; Lynnyk, Anna; Kratochvílová, Irena (Cryobiology, 2021)
For group of 281 oocytes obtained from 43 stimulated donors and cryopreserved by vitrification protocol using Cryotop and Kitazato medium we determined important parameters of oocytes collection and vitrification processes which strongly affect the probability that warmed oocytes will produce high-quality embryos for transfer. The probability to obtain high-quality embryos for transfer from vitrified and warmed oocytes was highest when two conditions were fulfilled: 1. oocytes were incubated before vitrification for 7-10 h and 2. stimulated ovaries of donors in one cycle produced a smaller number of oocytes (<7 oocytes from one donor per stimulated cycle). The probable reasons for these observations were: 1. early vitrification (less than 7 h) before final oocyte metaphase II maturation negatively affected the crucial process of post-warm remodelling of spindles and chromosomes, which reduced the fertilization and utilization rates, 2. the evaluated vitrification protocol amplifies negative impact of membrane defects of oocytes of those cohorts containing more than 6 oocytes - freezing places great demands on the integrity and elasticity of the cell membranes. The fact that cryopreservation influences a complex state of oocytes was confirmed by confocal microscopy.
Keywords: oocyty; Vitrification; vitrifikace; Metaphase; kryoprezervace; Oocytes; metafáze; Cryopreservation; Fertilization in Vitro; fertilizace in vitro